Sudden cardiac death in sports: Not a fatality! - Ghorayeb, N.; de Souza Colombo, C. S. S.; Contesini Francisco, R.; Ghorayeb Garcia, T. (International Journal of Cardiovascular Sciences, 2019)
Sudden cardiac death in sports is still controversial. Despite being a rare event, the death of an apparently healthy young athlete causes a major impact on the media. On the other hand, for being a rare event, it is clearly undervalued. Sports preparticipation cardiological assessment is one of the most effective preventive medical actions for professional and amateur endurance athletes. The regular and supervised practice of physical exercise does not kill. We believe that deaths are triggered by excessive physical training and use of drugs, in individuals with not diagnosed or undervalued heart diseases. It is necessary to make health professionals and athletes aware of the athletes' physiological limits, in addition to preparing the athletes properly when they try to overcome human limits.